The ATP-Dependent HslVU/ClpQY Protease Participates in Turnover of Cell Division Inhibitor SulA in Escherichia coli - Kanemori, Masaaki (American Society for Microbiology (ASM), 1999)
Escherichia coli mutants lacking activities of all known cytosolic ATP-dependent proteases (Lon, ClpAP, ClpXP, and HslVU), due to double deletions [ΔhslVU and Δ(clpPX-lon)], cannot grow at low (30°C) or very high (45°C) temperatures, unlike those carrying either of the deletions. Such growth defects were particularly marked when the deletions were introduced into strain MG1655 or W3110. To examine the functions of HslVU and other proteases further, revertants that can grow at 30°C were isolated from the multiple-protease mutant and characterized. The revertants were found to carry a suppressor affecting either ftsZ (encoding a key cell division protein) or sulA (encoding the SulA inhibitor, which binds and inhibits FtsZ). Whereas the ftsZ mutations were identical to a mutation known to produce a protein refractory to SulA inhibition, the sulA mutations affected the promoter-operator region, reducing synthesis of SulA. These results suggested that the growth defect of the parental double-deletion mutant at a low temperature was due to the accumulation of excess SulA without DNA-damaging treatment. Consistent with these results, SulA in the double-deletion mutant was much more stable than that in the Δ(clpPX-lon) mutant, suggesting that SulA can be degraded by HslVU. As expected, purified HslVU protease degraded SulA (fused to the maltose-binding protein) efficiently in an ATP-dependent manner. These results suggest that HslVU as well as Lon participates in the in vivo turnover of SulA and that HslVU becomes essential for growth when the Lon (and Clp) protease level is reduced below a critical threshold.